Reflection on the State of Islam and Muslim Scholars in Continuing the Islamic Tradition in Arawa Land, Nigeria - Suwaiba Salihu Kangiwa; Atiku Garba Yahaya (Universitas Ahmad Dahlan, 2021)
The study aimed to identify the contributions of scholars on the State of Islam and Muslim Scholars in Continuing the Islamic Tradition in Arawa Land. The paper attempted to brings into limelight the various contributions of Islamic scholars from North Africa (Maghrib) the entrenchment Islamic teachings in Arawaaland particularly the Wangarawa traders and Muhammad Kanta, Askia Muhammad, Muhammad bn Abd al-karim al Maghili. Also discussed in the paper, was the role played by the Sokoto Jihad scholars to the development of Islam and Islamic tradition in Arawa Land. However, the outcomes confirmed that, Arawa Land is currently witnessing the proliferation Muslim scholars and preachers whose proselytization activities have continued to impact positively on the life of the people. The researchers sourced data from the secondary sources as well interview complemented by observation and analyzed them. It is on the basis of such that, the findings of this research have portrayed the various contributions of Muslim scholars to the development of Islam and Islamic tradition in Arawa Land